Factors Influencing Procurement Officers’ Preference for PPP Procurement Model: An Empirical Analysis of China - Cao, Fuguo; Wang, Cong (Frontiers in Psychology, 2022)
The selection of the procurement model, which is a process of discretion exercised by procurement officials, is crucial to the PPP procurement performance. From theoretical analysis and international practice, we could find that the negotiation method is more suitable for complex PPP projects while the tendering method is widely used in China’s PPP procurement. To analyze the reasons for the phenomenon, we used the logit regression model to examine the influence of the regulatory competition, risk aversion preference and tacit interaction on the procurement model selection based on the data of 8926 PPP projects from 2009 to 2021 in China. The results indicate that regulatory competition leads to the confusion of procurement model selection, while risk aversion preference and tacit interaction significantly promote the application of tendering. Moreover, the heterogeneity analysis of regions and return models prove that provincial capitals and municipalities are more susceptible to regulatory competition, risk aversion preference and tacit interaction than ordinary cities. Compared with user-pay projects, government-pay projects and viability gap funding projects are more susceptible to regulatory competition and risk aversion preference, and less affected by tacit interaction. Therefore, to optimize the procurement model selection, policymakers should improve procurement policies to reduce the adverse effects of regulatory competition, risk aversion preference and tacit interactions.